2023
DOI: 10.7862/rm.2023.19
|View full text |Cite
|
Sign up to set email alerts
|

Investigating mechanical and physical properties of stir casted Al6061/nano Al2O3/quartz hybrid composite

Dagim Tirfe,
Abraham Woldeyohannes,
Bonsa Hunde
et al.

Abstract: Aluminum alloys are widely used in different engineering application areas, such as aerospace, automotive, and marine industries. However, their properties need some improvement in order to enlarge their application area. Thus, the objective of the study was to improve the physical and mechanical properties of Al6061 aluminum alloy by reinforcing it with nano-Al2O3 and micro-quartz particles. The investigation primarily was focused on studying the impact of quartz particles on the mechanical and physical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Malaki et al reported that the inclusion of nano SiO 2 particles improved AMCs' tensile and compressive strength [27]. Tirfe et al prepared Al6061/Al 2 O 3 /quartz hybrid AMCs and concluded that the hardness, compressive and impact strength of the AMCs improved with the addition of the optimum content of quartz particles [28]. Fly ash, a type of industrial waste, is yet another promising reinforcing material that has found increased usage to reinforce AMCs in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Malaki et al reported that the inclusion of nano SiO 2 particles improved AMCs' tensile and compressive strength [27]. Tirfe et al prepared Al6061/Al 2 O 3 /quartz hybrid AMCs and concluded that the hardness, compressive and impact strength of the AMCs improved with the addition of the optimum content of quartz particles [28]. Fly ash, a type of industrial waste, is yet another promising reinforcing material that has found increased usage to reinforce AMCs in recent years.…”
Section: Introductionmentioning
confidence: 99%